Relationship Between Nutritional Status, Exercise Level and Recreational Level with Dysmenorrhea in Nursing Students at Airlangga University - Pitaloka, Sekar Ayu; Triharini, Mira; Nimah, Lailatun (Pediomaternal Nursing Journal, 2022)
Introduction: Dysmenorrhea is a pain that occurs when a woman experiences menstruation with characteristics of pain that is felt before or during menstruation in a short time. It caused by a poor physiological condition. This study aims to analyzed the relationship between nutritional status, exercise level and recreation level with dysmenorrhea. Methods: This research was an analytic survey with cross sectional design. The number of samples taken were 116 students who fit the inclusion criterias, they were students of regular nursing faculty in the 2019 class, 18 and 19 years old and not yet married. Exclusion criteria included being pregnant and undergoing hormonal therapy. Instrument for dysmenorrhea using the Numeric Rating Scale (NRS) and questionnaire. Measurement nutritional status using the Mid Upper Arm Circumference (MUAC). Exercise and recreation also use a questionnaire as an instrument. Data were analyzed using Spearman Rho test with a significant α=0.05. This study was conducted at one of the public universities in Surabaya East Java. Results: The result of the analysis of nutritional status, exercise level and recreation level were showed a significant relationship, nutritional status (r=0.206, p=0.026), exercise level (r=-0.224, p=0.015) and recreation level (r=-0.272, p=0.003). Conculusion: Dysmenorrhea. Poor nutritional levels were tended to increase dysmenorrhea, less exercise levels were tended to cause severe dysmenorrhea and less recreational levels were also tended to cause severe dysmenorrhea. Health education about fulfilling nutrition, maintaining health by continuing to exercise and making time for recreation will reduce the risk of dysmenorrhea.